Environmental Microbiology - Reineke, Walter; Schlomann, Michael (Berlin: Springer Spektrum, 2023)
This textbook addresses global and local environmental problems and the involvement of microorganisms in their development and remediation. In particular, methodological aspects, some of them molecular genetic, for the study of microbial communities are considered. Overall, the prominent role of microorganisms in various material cycles is presented. In addition to biochemical principles for the degradation of environmental pollutants, the use of microorganisms in environmental biotechnological processes for the purification of air, water or soil as well as in environmentally friendly production processes is discussed. The book is intended for biologists with an interest in environmental microbiological issues, but also for students of process or environmental engineering, geoecology or geology, as well as students of other environmental science disciplines. For the 3rd edition, the authors have completely revised, corrected, updated and supplemented the book.
Keywords: Environmental microbiology; Microbial ecology; Biodegradation; Bioremediation